Who are your Students in Writing? - Damayanti, Rika; Mulyadi; Simaibang, Baginda (Jurnal Pendidikan Tambusai, 2021)
This study investigated the correlation among personality types, learning styles and writing ability to the eleventh grade students at Senior High School Number 1 Sekayu. The aims of this study were to measure the correlation between personality types and writing ability, the correlation between learning styles and writing ability, the correlation between personality types and learning styles, and the correlation among personality types, learning styles, and writing ability. In this study, the writer used purposive technique sampling. The data were collected by using questionnaire and test. The data were analyzed by using r-product moment and multiple regressions. The findings of this study are: 1. There was not any significant correlation between personality types and writing ability of the eleventh grade students at Senior High at Senior High School 1 Sekayu. 2. There was not any significant correlation between learning styles and writing ability of the eleventh grade students at Senior High School 1 Sekayu. 3. There was significant correlation between learning styles and writing ability of the eleventh grade students at at Senior High School 1 Sekayu. 4. There were not any significant correlations among personality types, learning styles, and writing ability of the eleventh grade students at Senior High School Number 1 Sekayu. It could be concluded that personality types and learning styles were not correlated significantly with students’ writing ability.